Preparation method of aerogel spherical porous carbon, preparation method of aerogel spherical silicon carbon negative electrode material and battery
Aerogel spherical porous carbon was prepared by sol-gel method, and aerogel spherical silicon carbon negative electrode material was prepared using this porous carbon, which solved the problems of low structural strength and poor pore consistency in the existing porous carbon preparation methods, and achieved a negative electrode material with high pore capacity, uniform pore size and low expansion rate, which improved the performance of the battery.
Patent Information
- Application Number
- CN202411929788.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-25
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2044-12-25
AI Technical Summary
The existing porous carbon preparation methods have problems such as low structural strength, poor pore consistency, high expansion rate, and poor electrochemical performance. In the process of silicon vapor deposition and carbon vapor coating, the uneven particle size distribution of porous carbon leads to poor product performance.
Aerogel spherical porous carbon was prepared by sol-gel method. Porous carbon with high pore volume, uniform pore size, regular spherical and low ash was prepared by precursor synthesis, solvent replacement, drying and dehydration, alkali activation pore formation, gas-phase ashing and physical activation, and porous carbon was used to prepare aerogel spherical silicon carbon anode material.
The prepared aerogel spherical porous carbon has high pore capacity, uniform pore size, regular spherical shape and low ash content. The aerogel spherical silicon carbon anode material used to prepare exhibits excellent effects such as lower resistivity, high capacity, high cycle life and low expansion.
Smart Images

Figure BDA0005210058880000141 
Figure BDA0005210058880000151 
Figure BDA0005210058880000161
Abstract
Description
Technical Field
[0001] The present application belongs to the field of biomass refining and comprehensive utilization, and specifically relates to a method for preparing aerogel spherical porous carbon, a method for preparing aerogel spherical silicon-carbon negative electrode material, and a battery. Background Art
[0002] The theoretical capacity of graphite negative electrode of lithium-ion battery is 375mAh / g, and the high lithium embedding capacity of silicon can meet the high capacity requirements of negative electrode of lithium battery in the future. At present, most of the new silicon-carbon negative electrode materials use porous carbon as the substrate, and perform vapor deposition in an atmosphere containing silicon source to deposit nano-silicon into the porous carbon pores, and then perform vapor coating in an atmosphere containing carbon source to wrap a layer of carbon layer on the surface of the material. The obtained silicon-carbon composite material is used as the negative electrode material of the battery, which can achieve high capacity and long cycle life, and can effectively improve the high expansion and low rate disadvantages of silicon-based negative electrode materials.
[0003] On the one hand, the pore structure of porous carbon needs to have good adsorption capacity for silicon source gas to ensure that the reaction process of silicon source gas cracking into nano-silicon occurs inside the porous carbon pores. This places high demands on the structural parameters of porous carbon. If the structure of porous carbon is not ideal, silicon will be deposited on the surface of the material, resulting in floating silicon, which will lead to deterioration of material processing performance and cycle life. On the other hand, silicon-containing source gas needs to have sufficient gas-solid contact with porous carbon, which places high demands on the fluidity of porous carbon materials. If the material fluidity is poor, it is easy to agglomerate and clump in the equipment, resulting in uneven reaction during silicon vapor deposition and carbon vapor coating, and poor product performance.
[0004] At present, coconut shell charcoal, resin, etc. are mostly used as precursors in the preparation of porous carbon. The activation methods include steam activation, CO2 activation and alkali activation. The equipment used for activation includes roller kilns, rotary kilns and other kilns. Porous carbon prepared by different processes has different disadvantages. For example, the porous carbon prepared by coconut shell charcoal has low structural strength and poor consistency of pore structure. The prepared new silicon-carbon negative electrode has high expansion rate and poor electrochemical performance. The pore structure of pore formation by water vapor and CO2 activation alone is uncontrollable. The prepared porous carbon has a large average pore size and a low proportion of micropores, which will lead to poor cycle performance of the prepared new silicon-carbon negative electrode. The pore formation process of alkali activation is complicated, the product ash content is high, and the wastewater is difficult to treat.
[0005] In addition, since silicon vapor deposition and carbon vapor coating need to be carried out at a certain gas flow rate, there are strict requirements on the particle size distribution of porous carbon. If the difference between the porous carbon Dv90 and Dv10 is too large, the particle size distribution is too wide, and there are more fine powders compared to Dv50, it will significantly affect the effects of silicon deposition and carbon coating, resulting in poor product performance. Therefore, after the porous carbon is prepared and before silicon vapor deposition, the porous carbon needs to be crushed and graded, resulting in a large amount of cost waste. Summary of the invention
[0006] In order to solve the problems in the prior art, the present application provides a method for preparing aerogel spherical porous carbon, a method for preparing aerogel spherical silicon-carbon negative electrode material, and a battery. The technical solution of the present application is as follows:
[0007] 1. A method for preparing aerogel spherical porous carbon, comprising:
[0008] Precursor synthesis steps: adding polymerization monomers, cross-linking agents, catalysts, and dispersants into water and stirring, and obtaining a synthetic mother solution containing a spherical aerogel precursor by a sol-gel method;
[0009] Solvent replacement step: centrifugally filtering the synthetic mother liquor to obtain a filter cake, mixing the filter cake with an alkaline pore-forming agent, adding an organic solvent and stirring and mixing to form the slurry;
[0010] Drying and dehydrating step: drying and dehydrating the slurry under a protective atmosphere to obtain a dried and dehydrated spherical aerogel precursor;
[0011] Alkali activation pore-forming step: in a protective atmosphere and at an activation temperature, the dried and dehydrated spherical aerogel precursor is subjected to alkali activation using an alkaline pore-forming agent rich in the spherical aerogel precursor;
[0012] Gas phase deashing step: adding acidic gas under protective atmosphere, so that the acidic gas and impurities generate salt and are gasified and removed, to obtain a spherical aerogel precursor after gas phase deashing;
[0013] Physical activation step: physically activating the spherical aerogel precursor after the gas phase deashing to obtain aerogel microsphere porous carbon.
[0014] 2. The preparation method according to item 1, wherein:
[0015] The polymerizable monomer is selected from any one or a combination of two or more of phenol, resorcinol, hydroquinone, catechol, melamine, cresol, and 2,4-dihydroxybenzoic acid;
[0016] The cross-linking agent is selected from any one or a combination of two or more of formaldehyde, paraformaldehyde, glutaraldehyde, hexamethylenetetramine, p-divinylbenzene, azobisisobutyl cyanide, and furfural;
[0017] The catalyst is selected from any one or a combination of two or more of sodium carbonate, potassium carbonate, sodium bicarbonate, potassium bicarbonate, potassium hydroxide, calcium hydroxide, and sodium hydroxide; and / or,
[0018] The dispersant is selected from any one or more of gelatin, polyvinyl alcohol, polyethylene glycol, white oil, hydroxypropyl methylcellulose, polyvinyl pyrrolidone, sodium polyacrylate, sodium dodecylbenzene sulfonate, sodium dodecyl sulfate, sorbitan oleate, polyacrylamide and cyclohexane.
[0019] 3. The preparation method as described in item 1, wherein:
[0020] The precursor synthesis step is carried out in a closed reactor under a protective atmosphere; the reaction temperature is 0 to 30° C., preferably 0 to 25° C.; the reaction time is 24 to 96 hours, preferably 48 to 72 hours.
[0021] 4. The preparation method according to item 1, wherein:
[0022] The alkaline pore-forming agent is selected from any one or a combination of two or more of potassium hydroxide, sodium hydroxide, potassium carbonate, sodium carbonate, potassium bicarbonate, and sodium bicarbonate;
[0023] The organic solvent is selected from any one or a combination of two or more of isoamyl alcohol, ethanol, methanol, acetone, cyclohexane, n-dodecane, dimethyl carbonate, diethyl carbonate, and ethylene carbonate; and / or,
[0024] The stirring and mixing in the solvent replacement step is carried out at 25 to 40° C. for 12 to 96 hours, preferably 48 to 72 hours.
[0025] 5. The preparation method according to item 1, wherein:
[0026] The drying and dehydration step is carried out in an activated fluidized bed; the drying and dehydration step includes a drying sub-step and a dehydration sub-step carried out after the drying sub-step; wherein,
[0027] In the drying sub-step, the slurry is sprayed into the activated fluidized bed through a two-fluid atomizing nozzle under a protective atmosphere; the drying temperature is 40 to 80° C.; the drying time after the slurry is completely in the activated fluidized bed is 0.5 to 12 hours;
[0028] The dehydration temperature of the dehydration sub-step is 200-800° C., preferably 300-600° C.; the dehydration time is 0.5-6 hours.
[0029] 6. The preparation method according to item 1, wherein:
[0030] The alkali-activated pore-forming step is carried out in an activated fluidized bed;
[0031] The activation temperature is set to 600-1000°C, preferably 750-950°C;
[0032] The activation time is 0.5 to 24 hours.
[0033] 7. The preparation method according to item 6, wherein:
[0034] In the alkali-activated pore-forming step, protective atmosphere gas is continuously introduced from the bottom of the gas-activated fluidized bed.
[0035] 8. The preparation method according to item 1, wherein:
[0036] The gas phase deashing step is carried out in an activated fluidized bed;
[0037] The gas phase deashing temperature is 600-1100°C, preferably 650-950°C;
[0038] The decalcification time is 0.5 to 6 hours.
[0039] 9. The preparation method according to item 1, wherein:
[0040] The acidic gas is derived from halogen elements and / or halogen compounds; wherein,
[0041] The halogen element is selected from any one or a combination of two or more of fluorine, chlorine, bromine and iodine, preferably chlorine;
[0042] The halogen compound is selected from any one of hydrogen fluoride, hydrogen chloride, hydrogen bromide, hydrogen iodide, chlorine fluoride, iodine chloride, iodine bromide, bromine chloride, and an acidic precursor compound, or a combination of two or more thereof, preferably hydrogen chloride; wherein the acidic precursor compound can be decomposed by heat in the alkali activation pore-forming step to produce at least one of hydrogen fluoride, hydrogen chloride, hydrogen bromide, hydrogen iodide, chlorine fluoride, iodine chloride, iodine bromide, and bromine chloride.
[0043] 10. The preparation method according to item 1, wherein:
[0044] The physical activation step is carried out in an activated fluidized bed, and a mixed gas of a protective atmosphere gas and an activator gas is introduced from the bottom of the fluidized bed, wherein the activated gas includes air and / or carbon dioxide; and / or,
[0045] The temperature of physical activation is 300-900° C., preferably 400-800° C.; the physical activation time is 0.5-6 h.
[0046] 11. A method for preparing an aerogel spherical silicon-carbon negative electrode material, which uses the aerogel spherical porous carbon prepared by any one of the methods for preparing aerogel spherical porous carbon in items 1 to 10, comprising:
[0047] Silicon vapor deposition step: introducing silicon source gas under a protective atmosphere to deposit silicon on the aerogel spherical porous carbon to obtain aerogel spherical porous carbon with nano-silicon deposition;
[0048] Carbon gas phase coating step: introducing carbon source gas under a protective atmosphere to carbon coat the aerogel spherical porous carbon deposited with nano-silicon to obtain the aerogel spherical silicon-carbon negative electrode material.
[0049] 12. The preparation method according to item 11, wherein:
[0050] The silicon vapor deposition step is carried out in a deposition fluidized bed;
[0051] The silicon source gas introduced under protective atmosphere is:
[0052] A mixed gas of protective atmosphere gas and the silicon source gas is introduced from the bottom of the deposition fluidized bed; the volume ratio of the protective atmosphere gas to the silicon source gas in the mixed gas is 10:(0.1-10).
[0053] 13. The preparation method according to item 11, wherein:
[0054] The carbon vapor coating step is carried out in a deposition fluidized bed;
[0055] The carbon source gas introduced under protective atmosphere is:
[0056] A mixed gas of protective atmosphere gas and the carbon source gas is introduced from the bottom of the deposition fluidized bed; the volume ratio of the protective atmosphere gas to the carbon source gas in the mixed gas is 10:(0.1-10).
[0057] 14. The preparation method according to item 11, wherein:
[0058] The silicon source gas is selected from silane and / or chlorosilane; and / or,
[0059] The carbon source gas is selected from one or a combination of two or more of alkanes, alkenes, alkynes and carbon oxides.
[0060] 15. A battery comprising:
[0061] An aerogel spherical silicon-carbon negative electrode material prepared by any method for preparing an aerogel spherical silicon-carbon negative electrode material in items 11 to 14.
[0062] The present application provides a method for preparing aerogel spherical porous carbon. Compared with the prior art in which porous carbon is prepared by using coconut shell charcoal, resin, etc. as precursors, the aerogel spherical porous carbon prepared by the preparation method of the present application has the advantages of high pore volume, appropriate and uniform pore size, regular spherical shape (good fluidity), low ash content, appropriate and concentrated particle size distribution (no need for crushing and grading screening), and high single particle strength; and provides a method for further preparing aerogel spherical silicon-carbon negative electrode material by using the aerogel spherical porous carbon prepared by the above method. The negative electrode material prepared by the preparation method has excellent effects such as lower resistivity, high capacity, high cycle life, and stronger restriction ability (low expansion rate) of internal silicon embedded lithium expansion. The battery prepared by the preparation method has higher discharge capacity, charging capacity and first efficiency.
[0063] The above description is only an overview of the technical solution of the present application. In order to make the technical means of the present application clearer and to enable those skilled in the art to implement it according to the contents of the specification, and to make the above and other purposes, features and advantages of the present application more obvious and easy to understand, the specific implementation methods of the present application are exemplified below. BRIEF DESCRIPTION OF THE DRAWINGS
[0064] Figure 1 : Electron microscopic image of aerogel microsphere porous carbon in Example 1;
[0065] Figure 2 : Electron microscopic image of aerogel microsphere porous carbon in Example 1;
[0066] Figure 3 : Electron microscopic image of aerogel microsphere porous carbon in Example 1;
[0067] Figure 4 : Electron microscopic image of aerogel microsphere porous carbon in Example 2;
[0068] Figure 5 : Electron microscopic image of aerogel microsphere porous carbon in Example 2;
[0069] Figure 6 : Electron microscopic image of aerogel microsphere porous carbon in Example 3;
[0070] Figure 7 : Electron microscopic image of aerogel microsphere porous carbon in Example 3;
[0071] Figure 8 : Electron microscopy image of porous carbon in Comparative Example 3;
[0072] Fig. 9 : Electron microscopy image of porous carbon in Comparative Example 3;
[0073] Fig.10 : Electron microscopy image of porous carbon in Comparative Example 4;
[0074] Fig.11 : Electron microscopy image of porous carbon in Comparative Example 4;
[0075] Fig.12 : SEM image of the aerogel precursor in Comparative Example 5. DETAILED DESCRIPTION
[0076] The best mode of the present invention will be shown and described below. Unless otherwise defined, all terms and scientific and technical terms used in this application have the same meaning as those skilled in the art to which the present invention belongs. In the event of inconsistency, the present application (including definitions) takes precedence.
[0077] Definitions of terms particularly used in this specification and / or basic technical contents are described below as appropriate.
[0078] In this application, the "sol-gel method" refers to using compounds containing highly chemically active components as precursors, uniformly mixing these raw materials in a liquid phase, and carrying out hydrolysis and condensation chemical reactions. Under a specific solvent system, the precursor forms a gel with a three-dimensional network structure, and agglomerates into spheres under the action of reverse phase to form gel microspheres.
[0079] In this application, "drying" refers to evaporating water, and "dehydration" refers to removing crystal water in the structure of alkali salts, etc. at high temperature.
[0080] In the present application, "alkaline pore former" refers to an additive that forms a pore structure by adding alkaline substances that can decompose or burn out at high temperature or under specific conditions during the preparation of the material, and specific examples include sodium hydroxide, potassium hydroxide, sodium carbonate, potassium carbonate, etc.
[0081] In the present application, "protective atmosphere" refers to the use of nitrogen and / or rare gases for protection. Among them, those skilled in the art know that rare gases can be listed, for example, helium (He), neon (Ne), argon (Ar), krypton (Kr), xenon (Xe), etc. From an economic point of view, the present application preferably uses nitrogen as the gas of the protective atmosphere.
[0082] In this application, "physical activation" is a material preparation process that removes some carbon atoms and increases the porosity and specific surface area of the material through the high-temperature reaction of an activator gas (such as an oxidizing gas (such as air) and / or a weak oxidizing gas (such as carbon dioxide)) with a carbon-based material.
[0083] In this application, "activated fluidized bed" refers to a low-speed fluidized bed in which a high-speed gas flow is introduced into the gas distributor at the bottom of the fluidized bed to fluidize the solid particles and fully contact them with the gas.
[0084] In the present application, "sedimented fluidized bed" refers to a low-speed stirred fluidized bed, in which a high-speed gas flow is introduced through a gas distributor at the bottom of the fluidized bed, and the dispersion effect of the stirring paddles at the bottom causes the solid particles to enter a fluidized state and come into full contact with the gas.
[0085] The following embodiments are provided to better understand the present invention, and the scope of the present application should not be limited to the following description. Therefore, it is obvious that those skilled in the art can refer to the description in this specification and appropriately change within the scope of the present invention. In addition, the following embodiments of the present invention can also be used alone or in combination.
[0086] In one aspect of the present application, a method for preparing aerogel spherical porous carbon is provided, comprising: a precursor synthesis step: adding a polymerization monomer and a cross-linking agent, a catalyst, and a dispersant into water and stirring, and obtaining a synthetic mother liquor containing a spherical aerogel precursor by a sol-gel method; a solvent replacement step: centrifugally filtering the synthetic mother liquor to obtain a filter cake, mixing the filter cake with an alkaline pore-forming agent, adding an organic solvent and stirring and mixing to form the slurry; a drying and dehydration step: drying the slurry under a protective atmosphere. and dehydration to obtain a dried and dehydrated spherical aerogel precursor; an alkali activation pore-forming step: under a protective atmosphere and an activation temperature, the dried and dehydrated spherical aerogel precursor is subjected to alkali activation using an alkaline pore-forming agent that is rich in the spherical aerogel precursor; a gas phase deashing step: adding an acidic gas under a protective atmosphere, causing the acidic gas and impurities to generate salts and gasify and remove them, to obtain a gas phase deashed spherical aerogel precursor; a physical activation step: physically activating the gas phase deashed spherical aerogel precursor to obtain aerogel microsphere porous carbon.
[0087] Compared with the prior art of preparing porous carbon by using coconut shell charcoal, resin, etc. as precursors and further obtaining silicon-carbon negative electrode materials, the above technical scheme of this embodiment uses a sol-gel method to prepare a spherical aerogel precursor rich in alkaline substances, regular morphology (spherical), concentrated particle size distribution, and high single particle strength, and utilizes the rich pore structure generated by the spherical aerogel precursor during synthesis, through further solvent replacement and alkali activation to form pores, and then uses a gas phase deashing process to remove a large amount of impurities including alkaline metals in the spherical aerogel precursor, and then uses physical activation to fine-tune the pore structure to prepare aerogel microsphere porous carbon with high pore volume, suitable and uniform pore size, regular spherical shape (good fluidity), low ash content, suitable particle size distribution (no need for crushing and grading screening) and concentrated, and high single particle strength, which is used to prepare a new silicon-carbon negative electrode material with lower resistivity, high capacity, high cycle life, and stronger restriction ability (low expansion rate) for internal silicon embedded lithium expansion.
[0088] In one embodiment, the polymerizable monomer prepared above is the main raw material in the precursor synthesis step, wherein the polymerizable monomer is selected from any one or a combination of two or more of phenol, resorcinol, hydroquinone, catechol, melamine, cresol, and 2,4-dihydroxybenzoic acid.
[0089] In one embodiment, the cross-linking agent is selected from any one or a combination of two or more of formaldehyde, paraformaldehyde, glutaraldehyde, hexamethylenetetramine, p-divinylbenzene, azobisisobutyl cyanide, and furfural, so as to ensure that the polymerized monomers are cross-linked and polymerized into macromolecular resins through active sites.
[0090] In one embodiment, the catalyst is selected from any one or a combination of two or more of sodium carbonate, potassium carbonate, sodium bicarbonate, potassium bicarbonate, potassium hydroxide, calcium hydroxide, and sodium hydroxide to increase the crosslinking speed of the polymerized monomer and adjust the particle size and internal pore structure.
[0091] In one embodiment, the dispersant is selected from any one or more of gelatin, polyvinyl alcohol, polyethylene glycol, white oil, hydroxypropyl methylcellulose, polyvinyl pyrrolidone, sodium polyacrylate, sodium dodecylbenzene sulfonate, sodium dodecyl sulfate, sorbitan oleate, polyacrylamide, and cyclohexane, so as to change the interfacial properties of the polymer when cross-linked, and to be able to independently form spheres in the solvent without sticking to each other;
[0092] In one embodiment, the precursor synthesis step is carried out in a closed reactor under a protective atmosphere; the reaction temperature is 0-30°C (specifically 0°C, 5°C, 10°C, 15°C, 20°C, 25°C, 30°C), preferably 0-25°C; the reaction time is 24-96h (specifically 25h, 30h, 35h, 40h, 45h, 50h, 55h, 60h, 65h, 70h, 75h, 80h, 85h, 90h, 95h), preferably 48-72h.
[0093] In one embodiment, the alkaline pore-forming agent is selected from any one of potassium hydroxide, sodium hydroxide, potassium carbonate, sodium carbonate, potassium bicarbonate, and sodium bicarbonate, or a combination of two or more thereof, so as to introduce the alkaline pore-forming agent into the spherical aerogel precursor to facilitate alkali activation pore formation in subsequent steps.
[0094] In one embodiment, the organic solvent is selected from any one or a combination of two or more of isoamyl alcohol, ethanol, methanol, acetone, cyclohexane, n-dodecane, dimethyl carbonate, diethyl carbonate, and ethylene carbonate.
[0095] In one embodiment, the stirring and mixing in the solvent replacement step is carried out at 25-40° C. (specifically 25° C., 30° C., 35° C., 40° C.) and the time is 12-96 h (specifically 15 h, 20 h, 25 h, 30 h, 35 h, 40 h, 45 h, 50 h, 55 h, 60 h, 65 h, 70 h, 75 h, 80 h, 85 h, 90 h, 95 h), preferably 48-72 h.
[0096] In one embodiment, the drying and dehydration step is carried out in an activated fluidized bed; the drying and dehydration step includes a drying sub-step and a dehydration sub-step carried out after the drying sub-step; wherein, in the drying sub-step, the slurry is sprayed into the activated fluidized bed through a two-fluid atomizing nozzle under a protective atmosphere; the drying temperature is 40 to 80°C (specifically, 40°C, 45°C, 50°C, 55°C, 60°C, 65°C, 70°C, 75°C, 80°C); after all the slurry enters the activated fluidized bed The drying time is 0.5 to 12 h (specifically 0.5 h, 1 h, 2 h, 3 h, 4 h, 5 h, 6 h, 7 h, 8 h, 9 h, 10 h, 11 h, 12 h); the dehydration temperature of the dehydration substep is 200 to 800 ° C (specifically 200 ° C, 300 ° C, 400 ° C, 500 ° C, 600 ° C, 700 ° C, 800 ° C), preferably 300 to 600 ° C; the dehydration time is 0.5 to 6 h (specifically 1 h, 2 h, 3 h, 4 h, 5 h, 6 h).
[0097] In one embodiment, the alkali activation pore-forming step is carried out in an activated fluidized bed; the activation temperature is set to 600-1000°C (specifically 600°C, 700°C, 800°C, 900°C, 1000°C), preferably 750-950°C; the activation time is 0.5-24h (specifically 1h, 2h, 3h, 4h, 5h, 6h, 7h, 8h, 9h, 10h, 11h, 12h, 13h, 14h, 15h, 16h, 17h, 18h, 19h, 20h, 21h, 22h, 23h, 24h).
[0098] In one embodiment, in the alkali-activated pore-forming step, a protective atmosphere gas is continuously introduced from the bottom of the gas-activated fluidized bed.
[0099] In one embodiment, the gas phase deashing step is carried out in an activated fluidized bed; the gas phase deashing temperature is 600-1100°C (specifically 600°C, 700°C, 800°C, 900°C, 1000°C, 1100°C), preferably 650-950°C; the deashing time is 0.5-6h (specifically 1h, 2h, 3h, 4h, 5h, 6h).
[0100] In one embodiment, the acidic gas comes from a halogen element and / or a halogen compound; wherein the halogen element is selected from any one or a combination of two or more of fluorine, chlorine, bromine and iodine elements, preferably chlorine; the halogen compound is selected from any one or a combination of two or more of hydrogen fluoride, hydrogen chloride, hydrogen bromide, hydrogen iodide, chlorine fluoride, iodine chloride, iodine bromide, bromine chloride, and an acidic precursor compound, preferably hydrogen chloride; wherein the acidic precursor compound can be decomposed by heat in the alkali activation pore-forming step to produce at least one of hydrogen fluoride, hydrogen chloride, hydrogen bromide, hydrogen iodide, chlorine fluoride, iodine chloride, iodine bromide, and bromine chloride.
[0101] In one aspect of the present application, a method for preparing an aerogel spherical silicon-carbon negative electrode material is provided, which uses the aerogel spherical porous carbon prepared by any of the above-mentioned embodiments, comprising: a silicon vapor deposition step: introducing a silicon source gas under a protective atmosphere, and performing silicon deposition on the aerogel spherical porous carbon to obtain aerogel spherical porous carbon with nano-silicon deposition; a carbon vapor coating step: introducing a carbon source gas under a protective atmosphere, and performing carbon coating on the aerogel spherical porous carbon with nano-silicon deposition to obtain the aerogel spherical silicon-carbon negative electrode material.
[0102] Based on the aerogel spherical porous carbon provided in the above embodiments, this embodiment further performs silicon vapor deposition and carbon vapor coating, so as to obtain an aerogel spherical silicon-carbon negative electrode material. Since the aerogel spherical porous carbon obtained in the above embodiments has the characteristics of high pore volume, suitable and uniform pore size, regular spherical shape (good fluidity), low ash content, suitable and concentrated particle size distribution (no need for crushing and grading screening), and high single particle strength, the aerogel spherical silicon-carbon negative electrode material obtained in this embodiment has excellent effects such as lower resistivity, high capacity, high cycle life, and stronger limiting ability (low expansion rate) of internal silicon embedded lithium expansion, so that it can be used to obtain batteries with better performance.
[0103] In one embodiment, the silicon vapor deposition step is carried out in a deposition fluidized bed; the silicon source gas is introduced under a protective atmosphere: a mixed gas of a protective atmosphere gas and the silicon source gas is introduced from the bottom of the fluidized bed; the volume ratio of the protective atmosphere gas to the silicon source gas in the mixed gas is 10:(0.1~10) (specifically 10:1, 10:2, 10:3, 10:4, 10:5, 10:6, 10:7, 10:8, 10:9, 10:10).
[0104] In one embodiment, the carbon vapor coating step is carried out in a deposition fluidized bed; the carbon source gas is introduced under a protective atmosphere: a mixed gas of a protective atmosphere gas and the carbon source gas is introduced from the bottom of the fluidized bed; the volume ratio of the protective atmosphere gas to the carbon source gas in the mixed gas is 10:(0.1~10) (specifically 10:1, 10:2, 10:3, 10:4, 10:5, 10:6, 10:7, 10:8, 10:9, 10:10).
[0105] In one embodiment, the silicon source gas is selected from silane and / or chlorosilane.
[0106] In one embodiment, the carbon source gas is selected from one or a combination of two or more of alkanes, alkenes, alkynes, and carbon oxides.
[0107] In addition, in the silicon vapor deposition step, the silicon vapor deposition temperature can be 450-650°C (specifically 450°C, 500°C, 550°C, 600°C, 650°C), preferably 500-550°C; in the carbon vapor coating step, the carbon coating temperature can be 450-700°C (specifically 450°C, 500°C, 550°C, 600°C, 650°C, 700°C), preferably 500-650°C.
[0108] In one aspect of the present application, a battery is provided, comprising: an aerogel spherical silicon-carbon negative electrode material prepared by any of the above-mentioned methods for preparing an aerogel spherical silicon-carbon negative electrode material. As can be seen from the comparison between the following examples and the comparative examples, the battery has higher discharge capacity, charge capacity and first efficiency.
[0109] Example
[0110] The experimental methods used below are conventional methods unless otherwise specified.
[0111] Unless otherwise specified, the materials and reagents used below can be obtained from commercial sources.
[0112] Example 1
[0113] 19 kg of resorcinol, 1 kg of phenol, 12 kg of formaldehyde, 1 kg of sodium carbonate, 100 kg of deionized water, 50 L of sorbitan oleate, and 450 L of cyclohexane were added to the jacketed reactor. 25 ° C cold water was introduced into the jacket of the reactor for insulation. At the same time, high-purity nitrogen was used to replace the air in the reactor three times to ensure that the reaction was carried out under a nitrogen atmosphere.
[0114] After stirring the reaction liquid at 25°C for 72 hours, the solid matter was separated by centrifugation from the bottom of the reactor, the wet solid matter was mixed with 60 kg of industrial potassium hydroxide, and then added into 200 L of acetone for solvent replacement, and stirred at 25°C for 72 hours;
[0115] The slurry is conveyed to the activated fluidized bed heated to 40°C by pressure, and sprayed into the fluidized bed cavity under nitrogen protection through a two-fluid atomizing nozzle. After all the slurry is sprayed into the fluidized bed, the powder is dried at a constant temperature of 40°C for 12 hours. Then the activated fluidized bed is heated to 500°C at a rate of 8°C / min and kept at a constant temperature for 2 hours to dehydrate the powder. During drying and dehydration, nitrogen is continuously introduced into the bottom of the activated fluidized bed to purge the powder.
[0116] When dehydration is completed, the activation fluidized bed is heated to 700°C at a rate of 2°C / min and maintained for 12 hours. At the same time, nitrogen is introduced into the bottom of the activation fluidized bed to perform alkaline activation on the powder. After the alkaline activation is completed, the temperature is raised to 800°C at a rate of 2°C / min, and a mixed gas of HCl and nitrogen is introduced into the bottom of the activation fluidized bed. The volume ratio of HCl to nitrogen is 1.5:8.5. After maintaining for 4 hours, gas phase deashing is completed;
[0117] After the gas phase deashing is completed, a mixed gas of nitrogen and air is introduced from the bottom of the fluidized bed at the same time, with a volume ratio of nitrogen to air of 10:1, and physical activation is carried out at 800°C for 30 minutes. After the physical activation is completed, natural cooling begins;
[0118] The heating of the activated fluidized bed is turned off to reduce the temperature in the activated fluidized bed to below 100° C. to obtain aerogel spherical porous carbon, and the aerogel spherical porous carbon is transferred from the activated fluidized bed to the deposition fluidized bed by gas transport, and the fluidized bed is heated under the protection of a nitrogen atmosphere;
[0119] When the deposition fluidized bed is heated to 520°C, the temperature is kept constant, and a mixed gas of monosilane and nitrogen is introduced from the bottom of the deposition fluidized bed, the volume ratio of monosilane to nitrogen is 2:8, and silicon vapor deposition is carried out. After maintaining for 360 minutes, the introduction of monosilane is stopped, and the fluidized bed is heated to 600°C under a nitrogen atmosphere, the temperature is kept constant, and a mixed gas of acetylene and nitrogen is started to be introduced, the volume ratio of acetylene to nitrogen is 2:8, and carbon vapor coating is carried out. After maintaining for 360 minutes, the introduction of acetylene is stopped, and the heating of the fluidized bed is turned off. The fluidized bed is cooled down in a nitrogen atmosphere. When the temperature of the fluidized bed drops below 100°C, the reactor is discharged to obtain an aerogel spherical silicon-carbon negative electrode material.
[0120] Example 2
[0121] 15 kg of resorcinol, 5 kg of melamine, 12 kg of formaldehyde, 1 kg of sodium hydroxide, 100 kg of deionized water, 50 L of sorbitan oleate, and 450 L of cyclohexane were added to the jacketed reactor. 25 ° C cold water was introduced into the jacket of the reactor for insulation. At the same time, high-purity nitrogen was used to replace the air in the reactor three times to ensure that the reaction was carried out under a nitrogen atmosphere.
[0122] After stirring the reaction liquid at 25°C for 48 hours, the solid matter was separated by centrifugation from the bottom of the reactor, the wet solid matter was mixed with 60 kg of industrial potassium hydroxide, and then put into 200 L of acetone for solvent replacement, and stirred at 25°C for 72 hours;
[0123] The subsequent steps are the same as those in Example 1.
[0124] Example 3
[0125] 12 kg of resorcinol, 8 kg of 2,4-dihydroxybenzoic acid, 12 kg of formaldehyde, 1 kg of potassium hydroxide, 100 kg of deionized water, 50 L of sorbitan oleate, and 450 L of white oil were added to the jacketed reactor. 25° C. cold water was introduced into the jacket of the reactor for insulation. At the same time, high-purity nitrogen was used to replace the air in the reactor three times to ensure that the reaction was carried out under a nitrogen atmosphere.
[0126] After stirring the reaction liquid at 25°C for 24 hours, the material was discharged from the bottom of the reactor and the solid matter was separated by centrifugation. The wet solid matter was mixed with 60 kg of industrial potassium hydroxide, and then put into 200 L of acetone for solvent replacement, and stirred at 25°C for 72 hours.
[0127] The subsequent steps are the same as those in Example 1.
[0128] Comparative Example 1 (only introducing alkaline pore-forming agent without solvent replacement)
[0129] 19 kg of resorcinol, 1 kg of phenol, 12 kg of formaldehyde, 1 kg of sodium carbonate, 100 kg of deionized water, 50 L of sorbitan oleate, and 450 L of cyclohexane were added to the jacketed reactor. 25° C. cold water was introduced into the reactor jacket for insulation. At the same time, high-purity nitrogen was used to replace the air in the reactor three times to ensure that the reaction was carried out under a nitrogen atmosphere.
[0130] After the precursor is synthesized, 60 kg of potassium hydroxide is added to the reactor and stirring is continued at 25 °C for 72 hours. Then, the slurry is transported to the activated fluidized bed heated to 40 °C by pressure and sprayed into the fluidized bed cavity under nitrogen protection through a two-fluid atomizing nozzle. After all the slurry is sprayed into the fluidized bed, the powder is dried at a constant temperature of 40 °C for 12 hours. Then, the activated fluidized bed is heated to 500 °C at a rate of 8 °C / min and kept at a constant temperature for 2 hours to dehydrate the powder. During drying and dehydration, nitrogen is continuously passed through the bottom of the activated fluidized bed to purge the powder.
[0131] The subsequent steps are the same as those in Example 1.
[0132] Comparative Example 2 (no physical activation)
[0133] 19 kg of resorcinol, 1 kg of phenol, 12 kg of formaldehyde, 1 kg of sodium carbonate, 100 kg of deionized water, 50 L of sorbitan oleate, and 450 L of cyclohexane were added to the jacketed reactor. 25° C. cold water was introduced into the reactor jacket for insulation. At the same time, high-purity nitrogen was used to replace the air in the reactor three times to ensure that the reaction was carried out under a nitrogen atmosphere.
[0134] After stirring the reaction liquid at 25°C for 72 hours, the material was discharged from the bottom of the reactor and the solid matter was separated by centrifugation. The wet solid matter was mixed with 60 kg of industrial potassium hydroxide, and then put into 200 L of acetone for solvent replacement, and stirred at 25°C for 72 hours.
[0135] The slurry is conveyed to the activated fluidized bed heated to 40°C by pressure, and sprayed into the fluidized bed cavity through a two-fluid atomizing nozzle under nitrogen protection. After all the slurry is sprayed into the fluidized bed, the temperature is kept constant at 40°C for 12 hours to dry the powder. Then the activated fluidized bed is heated to 500°C at a rate of 8°C / min and kept constant for 2 hours to dehydrate the powder. During drying and dehydration, nitrogen is continuously passed through the bottom of the activated fluidized bed to purge the powder.
[0136] When dehydration is completed, the activation fluidized bed is heated to 700°C at a rate of 2°C / min and maintained for 12 hours. At the same time, nitrogen is introduced into the bottom of the activation fluidized bed to perform alkaline activation on the powder. After the alkaline activation is completed, the temperature is raised to 800°C at a rate of 2°C / min, and a mixed gas of HCl and nitrogen is introduced into the bottom of the activation fluidized bed. The volume ratio of HCl and nitrogen is 1.5:8.5. After maintaining for 4 hours, gas phase deashing is completed.
[0137] After the gas phase deashing is completed, no physical activation is performed and the temperature is directly lowered, and the subsequent steps are the same as those in Example 1.
[0138] Comparative Example 3 (Preparation of porous carbon using phenolic resin)
[0139] Use Shengquan Group's model PF4012 powdered resin precursor, solidify it into block resin at 120°C, and then crush it once. The obtained resin fragments are distilled at 500°C to obtain resin precursor fragments, which are crushed twice. 15kg of the crushed resin precursor powder and 60kg of industrial potassium hydroxide are mixed, put into 200L of acetone for solvent replacement, and stirred at 25°C for 72h.
[0140] The subsequent steps are the same as those in Example 1.
[0141] Comparative Example 4 (Preparation of non-spherical porous carbon using coconut shell charcoal)
[0142] Commercial coconut shell charcoal was crushed, and 15 kg of the obtained coconut shell charcoal powder was mixed with 60 kg of industrial potassium hydroxide, and then added into 200 L of acetone for solvent replacement, and stirred at 25° C. for 72 h.
[0143] The subsequent steps are the same as those in Example 1.
[0144] Comparative Example 5 (no dispersant used)
[0145] 15 kg of resorcinol, 5 kg of melamine, 12 kg of formaldehyde, 1 kg of sodium hydroxide and 600 kg of deionized water were added to the jacketed reactor. 25°C cold water was introduced into the reactor jacket for insulation. High-purity nitrogen was used to replace the air in the reactor three times to ensure that the reaction was carried out under a nitrogen atmosphere.
[0146] After stirring the reaction solution at 25° C. for 48 h, the solid matter was separated by centrifugation from the bottom of the reactor.
[0147] The subsequent steps are the same as those in Example 1.
[0148] Test example
[0149] Porous carbon performance testing
[0150] For the porous carbon of Examples 1 to 3 and Comparative Examples 1 to 4, the pore volume, specific surface area and micropore ratio of the porous carbon were detected using the ASAP2460 multi-station extended fully automatic specific surface and porosity analyzer produced by Micromeritics. The particle size distribution of the porous carbon was tested using the Malvern laser particle size analyzer Mastersizer 3000E. The test results are detailed in Table 1.
[0151] Table 1: Porous carbon test results
[0152]
[0153]
[0154] According to the performance comparison of porous carbon prepared in Examples 1 to 3 and Comparative Examples 3 to 4, it can be found that the aerogel spherical porous carbon will show certain differences in particle size distribution according to the different formulas used, but the difference between Dv90 and Dv10 is between 3.12 and 6.72, which is much smaller than Comparative Examples 3 to 4 (27.12 to 32.73). This is because in Examples 1 to 3 of the present application, the growth degree of the synthesized spherical aerogel precursor can be controlled in the precursor synthesis step to adjust the size of the microspheres, but the resin and coconut shell carbon precursors of Comparative Examples 3 to 4 need to be crushed to adjust the particle size. The narrower particle size distribution of the aerogel spherical porous carbon in Examples 1 to 3 is conducive to the uniformity of the preparation of silicon vapor deposition, and the prepared silicon-carbon negative electrode material has better consistency and processing performance.
[0155] In Comparative Example 1, no solvent replacement was performed, and the alkaline pore-forming agent was not fully mixed with the spherical aerogel precursor, resulting in poor alkaline activation effect. The pore volume and specific surface area of the prepared aerogel microsphere porous carbon were not as good as those in Example 1. The proportion of micropores in Comparative Example 2 is too high, indicating that there are fewer mesopores and macropores, and the average pore size is smaller. The precursors of Comparative Examples 3 to 4 are not aerogel microspheres. After the same activation process, the pore volume is lower than that of Example 1, and the proportion of micropores is only about 90%. Although the presence of mesopores and macropores is a channel for silicon to penetrate into the porous carbon during vapor deposition, a large proportion will cause the porous carbon to have a poor adsorption capacity for silane. At the same time, the difficulty of carbon coating increases, which is not conducive to the preparation of high-capacity silicon-carbon negative electrode materials.
[0156] Electron microscopy of porous carbon
[0157] The porous carbon obtained in Examples 1 to 3, Comparative Examples 3 to 4, and the aerogel precursor of Comparative Example 5 were analyzed using a field emission scanning electron microscope. The test results are detailed in Figures 1 to 12 .
[0158] It can be seen that the porous carbon obtained in Comparative Example 3 has more sharp edges, which is not conducive to the fluidization of the porous carbon in the deposition fluidized bed in the subsequent steps, and is not conducive to the uniform distribution during silicon vapor deposition; Comparative Example 4 uses coconut shell charcoal as a precursor. Due to the characteristics of biomass materials, it has naturally formed mesopores and macropores, which is not conducive to the adsorption of silane by porous carbon during silicon vapor deposition. In Comparative Example 5, no dispersant was added during the synthesis of aerogel microspheres, resulting in the formation of microspheres that adhered to each other and could not be used for the production of porous carbon. Compared with the porous carbon of Comparative Examples 3 to 5, the porous carbon (aerogel spherical porous carbon) prepared in Examples 1 to 3 of the present application is of suitable size and spherical, and is easy to fluidize in the deposition fluidized bed to facilitate silicon vapor deposition and carbon vapor coating.
[0159] Negative electrode materials and prepared battery performance testing
[0160] For the negative electrode materials prepared in Examples 1 to 3 and Comparative Examples 1 to 4, the specific surface area of the negative electrode materials was detected by using Micromeritics' ASAP2460 multi-station extended fully automatic specific surface and porosity analyzer, the carbon content of the negative electrode materials was detected by using a Carbon Sulfur Tester (3500) from Steel Research Institute, the single particle strength of the negative electrode materials was detected by using a Shimadzu MCT-210 micro compression testing machine, and button batteries prepared using the negative electrode materials were used to detect the electrical properties of the prepared batteries.
[0161] The preparation method of the button battery is as follows: the silicon-carbon negative electrode material: SP: CMC: LA136D is prepared into a slurry in a ratio of 75:10:2.5:12.5 (SP (Super carbon) is a conductive agent, CMC is carboxymethyl cellulose (CMC 2200), LA136D is an aqueous silicon-carbon negative electrode binder, and the materials are commonly used materials for the production of button batteries), the materials are homogenized in an Intet ITI-300SS vacuum stirring and degassing machine, and then a coating machine is used to coat the 9μm copper foil with a coating thickness of 120μm, and the foil coated with the slurry is dried and cut into The circular pole piece is made of lithium sheet, circular pole piece, ceramic PVDF diaphragm and LB-137 to assemble CR2032 battery. The specifications of lithium sheet are: Membrane specifications: base membrane 9μm, PVDF coating 3μm, ceramic layer 1μm, electrolyte specifications: 1M LiPF6 in DMC:EC:EMC=1:1:1Vol%with 5%FEC,1%VC, dosage: 60μL.
[0162] Table 2: Negative electrode material performance and battery performance test results
[0163]
[0164]
[0165] According to the performance comparison of the silicon-carbon negative electrode materials prepared in Examples 1 to 3 and Comparative Examples 1 to 4, it can be found that in Comparative Example 1, no solvent replacement was performed during alkali activation, the pore tolerance of the prepared porous carbon was poor, and the capacity of the prepared silicon-carbon material was low; Comparative Example 2 did not perform physical activation, the internal micropores accounted for a high proportion, and the average pore size was small, resulting in the generation of mainly amorphous silicon after silane cracking, with fewer silicon grains, which would affect the reversible capacity and first coulomb efficiency of the silicon-carbon material, resulting in poor reversible capacity of the material at the same silicon deposition amount, reduced first efficiency, and detrimental to product quality.
[0166] An appropriate micropore ratio is very important for the performance of silicon-carbon materials after silicon deposition, which is conducive to the adsorption of silane gas into the pores for decomposition. However, if the micropore ratio is too high (such as in Comparative Example 2 above), the excessively fine micropore diameters cannot allow silane gas molecules to pass through well, which can easily lead to an increase in invalid micropores, which is detrimental to the electrochemical performance of silicon-carbon materials. At the same time, silicon in the tiny micropores is mainly deposited in the form of amorphous silicon, and its reversible capacity and first effect are inferior to those of crystalline silicon. The embodiments of the present application can appropriately expand the pore diameter of the tiny micropores by physically activating and expanding the micropores to appropriately reduce the micropore ratio, so that silane can better pass through the pores into the deep of the porous carbon without significantly affecting the ability to adsorb silane gas. In addition, the increased mesoporous macropores can allow silicon to be deposited in the form of grains, better exerting electrochemical performance, and improving the reversible capacity and first effect of the silicon-carbon material.
[0167] Comparative Examples 3 and 4 use phenolic resin and coconut shell carbon as precursors, respectively, and the porous carbon prepared has a low pore volume, and the electrochemical performance of the silicon-carbon negative electrode material prepared thereby is poor.
[0168] Comparative Example 3 uses block phenolic resin as a porous carbon precursor, and the porous carbon prepared by crushing is non-spherical. The particle strength of the silicon-carbon material prepared by depositing silicon as a carrier is worse than that of the porous carbon prepared by aerogel microspheres. Comparative Example 4 uses biomass coconut shell charcoal as a porous carbon precursor, and the particle strength is lower than that of the resin precursor. When the silicon-carbon negative electrode material with low particle strength is used as a negative electrode material for a battery cell, silicon will expand during lithium insertion and de-lithiation. If the porous carbon has a low ability to restrain silicon expansion, it will lead to poor battery cell cycle performance and cannot meet the requirements of long-term use.
Claims
1. A method for preparing aerogel spherical porous carbon, comprising: Precursor synthesis steps: adding polymerization monomers, cross-linking agents, catalysts, and dispersants into water and stirring, and obtaining a synthetic mother solution containing a spherical aerogel precursor by a sol-gel method; Solvent replacement step: centrifugally filtering the synthetic mother liquor to obtain a filter cake, mixing the filter cake with an alkaline pore-forming agent, adding an organic solvent and stirring and mixing to form the slurry; Drying and dehydrating step: drying and dehydrating the slurry under a protective atmosphere to obtain a dried and dehydrated spherical aerogel precursor; Alkali activation pore-forming step: in a protective atmosphere and at an activation temperature, the dried and dehydrated spherical aerogel precursor is subjected to alkali activation using an alkaline pore-forming agent rich in the spherical aerogel precursor; Gas phase deashing step: adding acidic gas under protective atmosphere, so that the acidic gas and impurities generate salt and are gasified and removed, to obtain a spherical aerogel precursor after gas phase deashing; Physical activation step: physically activating the spherical aerogel precursor after the gas phase deashing to obtain aerogel microsphere porous carbon.
2. The preparation method according to claim 1, wherein The polymerizable monomer is selected from any one or a combination of two or more of phenol, resorcinol, hydroquinone, catechol, melamine, cresol, and 2,4-dihydroxybenzoic acid; The cross-linking agent is selected from any one or a combination of two or more of formaldehyde, paraformaldehyde, glutaraldehyde, hexamethylenetetramine, p-divinylbenzene, azobisisobutyl cyanide, and furfural; The catalyst is selected from any one or a combination of two or more of sodium carbonate, potassium carbonate, sodium bicarbonate, potassium bicarbonate, potassium hydroxide, calcium hydroxide, and sodium hydroxide; The dispersant is selected from any one or more of gelatin, polyvinyl alcohol, polyethylene glycol, white oil, hydroxypropyl methylcellulose, polyvinyl pyrrolidone, sodium polyacrylate, sodium dodecylbenzene sulfonate, sodium dodecyl sulfate, sorbitan oleate, polyacrylamide, and cyclohexane; and / or, The precursor synthesis step is carried out in a closed reactor under a protective atmosphere; the reaction temperature is 0 to 30° C., preferably 0 to 25° C.; the reaction time is 24 to 96 hours, preferably 48 to 72 hours.
3. The preparation method according to claim 1, wherein The alkaline pore-forming agent is selected from any one or a combination of two or more of potassium hydroxide, sodium hydroxide, potassium carbonate, sodium carbonate, potassium bicarbonate, and sodium bicarbonate; The organic solvent is selected from any one or a combination of two or more of isoamyl alcohol, ethanol, methanol, acetone, cyclohexane, n-dodecane, dimethyl carbonate, diethyl carbonate, and ethylene carbonate; and / or, The stirring and mixing in the solvent replacement step is carried out at 25 to 40° C. for 12 to 96 hours, preferably 48 to 72 hours.
4. The preparation method according to claim 1, wherein The drying and dehydration step is carried out in an activated fluidized bed; the drying and dehydration step includes a drying sub-step and a dehydration sub-step carried out after the drying sub-step; wherein, In the drying sub-step, the slurry is sprayed into the activated fluidized bed through a two-fluid atomizing nozzle under a protective atmosphere; the drying temperature is 40 to 80° C.; the drying time after the slurry is completely in the activated fluidized bed is 0.5 to 12 hours; The dehydration temperature of the dehydration sub-step is 200-800° C., preferably 300-600° C.; the dehydration time is 0.5-6 hours.
5. The preparation method according to claim 1, wherein The alkali activation pore-forming step is carried out in an activated fluidized bed; the activation temperature is set to 600-1000° C., preferably 750-950° C.; the activation time is 0.5-24 hours; Preferably, in the alkali-activated pore-forming step, a protective atmosphere gas is continuously introduced from the bottom of the gas-activated fluidized bed.
6. The preparation method according to claim 1, wherein The gas phase deashing step is carried out in an activated fluidized bed; the gas phase deashing temperature is 600-1100° C., preferably 650-950° C.; the deashing time is 0.5-6 hours; and / or, The acidic gas comes from halogen elements and / or halogen compounds; wherein the halogen elements are selected from any one or a combination of two or more of fluorine, chlorine, bromine and iodine elements, preferably chlorine; the halogen compounds are selected from any one or a combination of two or more of hydrogen fluoride, hydrogen chloride, hydrogen bromide, hydrogen iodide, chlorine fluoride, iodine chloride, iodine bromide, bromine chloride and acidic precursor compounds, preferably hydrogen chloride; wherein the acidic precursor compound can be decomposed by heat in the alkali activation pore-forming step to produce at least one of hydrogen fluoride, hydrogen chloride, hydrogen bromide, hydrogen iodide, chlorine fluoride, iodine chloride, iodine bromide and bromine chloride.
7. The preparation method according to claim 1, wherein The physical activation step is carried out in an activated fluidized bed, and a mixed gas of a protective atmosphere gas and an activator gas is introduced from the bottom of the fluidized bed, wherein the activated gas includes air and / or carbon dioxide; and / or, The temperature of physical activation is 300-900° C., preferably 400-800° C.; the physical activation time is 0.5-6 h.
8. A method for preparing an aerogel spherical silicon-carbon negative electrode material, using the aerogel spherical porous carbon prepared by the method for preparing an aerogel spherical porous carbon according to any one of claims 1 to 7, comprising: Silicon vapor deposition step: introducing silicon source gas under a protective atmosphere to deposit silicon on the aerogel spherical porous carbon to obtain aerogel spherical porous carbon with nano-silicon deposition; Carbon gas phase coating step: introducing carbon source gas under a protective atmosphere to carbon coat the aerogel spherical porous carbon deposited with nano-silicon to obtain the aerogel spherical silicon-carbon negative electrode material.
9. The preparation method according to claim 8, wherein The silicon vapor deposition step is carried out in a deposition fluidized bed; the silicon source gas is introduced under a protective atmosphere: a mixed gas of the protective atmosphere gas and the silicon source gas is introduced from the bottom of the deposition fluidized bed; the volume ratio of the protective atmosphere gas to the silicon source gas in the mixed gas is 10:(0.1-10); The carbon gas phase coating step is carried out in a deposition fluidized bed; the carbon source gas is introduced under a protective atmosphere: a mixed gas of the protective atmosphere gas and the carbon source gas is introduced from the bottom of the deposition fluidized bed; the volume ratio of the protective atmosphere gas to the carbon source gas in the mixed gas is 10:(0.1-10); The silicon source gas is selected from silane and / or chlorosilane; and / or, The carbon source gas is selected from one or a combination of two or more of alkanes, alkenes, alkynes and carbon oxides.
10. A battery comprising: An aerogel spherical silicon-carbon negative electrode material prepared by the method for preparing an aerogel spherical silicon-carbon negative electrode material according to any one of claims 8 to 9.
Citation Information
Patent Citations
Preparation method of spherical charcoal-aero gel
CN101041430A
Preparation of high specific surface carbon aerogel
CN101468795A
Porous carbon material produced from gasified coal slag, production method and application of porous carbon material produced from gasified coal slag
CN110668422A
Preparation method of carbon aerogel
CN111422853A
Preparation method of monatomic metal-nitrogen doped carbon aerogel electrocatalyst
CN113584514A
Cited By
Method for preparing silicon-carbon composite negative electrode material by using porous carbon airflow fine powder
CN120878767A